Symmetrical Apophyses on the Posterior Margins of the Thyroid Cartilage: A Previously Undescribed Anatomical Variation With Potential Forensic Implications. (March 2019) - Porzionato, Andrea; Macchi, Veronica; Mazzarolo, Cristina; Morra, Aldo; Sanudo, Jose; De Caro, Raffaele
Abstract : Abstract: Differential diagnosis between normal/variant anatomy and pathological/traumatic findings represents one of the main matters of investigation of the so-called forensic clinical anatomy. In the literature, many anatomical variations of the laryngeal thyroid cartilage have been reported, with potential implications in forensic pathology. They include triticeal cartilages, foramen thyroideum, asymmetry, segmentation or agenesis of the superior thyroid horns, bone connections with the hyoid bone, absence of cricothyroid facets, hypertrophy of the inferior thyroid tubercle, and asymmetries in the thyroid notch, isthmus, or length of the inferior horn. In this report, we describe a laryngeal anatomical variation never described before, consisting of 2 apophyses symmetrically arising from the posterior margins of the thyroid laminae. Postmortem computed tomography performed on the laryngeal visceral block excluded previous traumatic injuries or natural pathologies of the laryngeal cartilages, confirming the congenital origin of the finding. An "omega epiglottis" and 3 laryngeal cysts in the piriform sinuses also coexisted, suggesting the possibility of underlying common developmental mechanisms.